The effects of a task shifted multi-component mental health intervention to support prosthetic and orthotic service users in Cambodia: a non-randomised controlled study - Alan Maddock; Thearith Heang; Nil Ean; Sisary Kheng; Paul Best; Nerrolyn Ramstrand (International Journal of Mental Health Systems)
Abstract Background Mental health disorders are major public health challenges, particularly in low- and middle-income countries such as Cambodia, where chronic shortages in mental health services and human resources exist. These issues are compounded for marginalized groups such as persons with physical disabilities due to their being at a higher risk of psychological distress and PTSD symptoms. The development of effective and accessible mental health systems in Cambodia will require evidence-based culturally appropriate mental health interventions. There are insufficient good-quality studies which have been completed to draw firm conclusions about the effectiveness of culturally appropriate mental health interventions in Cambodia. The aim of this study was to evaluate the effectiveness of a task shifted multi-component mental health intervention (named ‘Friendship groups’) at reducing psychological distress and PTSD, worry, rumination and increasing mindfulness among cohort of prosthetic and orthotic (P&O) service users. Methods From March 2023 to June 2024 data (N = 465) were collected as part of a mental health screening programme for P&O service users across Cambodia. Participants experiencing mild to moderate psychological distress were screened and invited to participate in this study. Due to ethical considerations a non-randomised controlled trial design with repeated measures (pre-post intervention) was conducted to evaluate the effects of Friendship groups (N = 33) against a non-active control condition (N = 39). Results When compared to the control condition the Friendship groups were found to have a moderate to large effect on psychological distress, and a small to moderate effect on rumination. The Friendship group participants experienced reduced PTSD symptoms, worry and improved mindfulness post group but these changes were not significant when compared to the control condition. Conclusions The results from this study evidence the acceptability and effectiveness of Friendship groups at reducing psychological distress. Our results also provide clear guidance that if Friendship groups are implemented across P&O services in Cambodia, P&O service users are likely to experience reduced psychological distress. These findings also add to the growing literature supporting the need for culturally adapted task shifted mental health interventions in low- and middle-income countries, where access to specialised care remains limited.